The F-box protein Bard (CG14317) targets the Smaug RNA-binding protein for destruction during the Drosophila maternal-to-zygotic transition. Issue 1 (20th October 2021) - Cao, Wen Xi; Karaiskakis, Angelo; Lin, Sichun; Angers, Stephane; Lipshitz, Howard D
Abstract: During the maternal-to-zygotic transition (MZT), which encompasses the earliest stages of animal embryogenesis, a subset of maternally supplied gene products is cleared, thus permitting activation of zygotic gene expression. In the Drosophila melanogaster embryo, the RNA-binding protein Smaug (SMG) plays an essential role in progression through the MZT by translationally repressing and destabilizing a large number of maternal mRNAs. The SMG protein itself is rapidly cleared at the end of the MZT by a Skp/Cullin/F-box (SCF) E3-ligase complex. Clearance of SMG requires zygotic transcription and is required for an orderly MZT. Here, we show that an F-box protein, which we name Bard (encoded by CG14317), is required for degradation of SMG. Bard is expressed zygotically and physically interacts with SMG at the end of the MZT, coincident with binding of the maternal SCF proteins, SkpA and Cullin1, and with degradation of SMG. shRNA-mediated knock-down of Bard or deletion of the bard gene in the early embryo results in stabilization of SMG protein, a phenotype that is rescued by transgenes expressing Bard. Bard thus times the clearance of SMG at the end of the MZT. Abstract : Degradation of the Smaug RNA-binding protein is essential for an orderly maternal-to-zygotic transition (MZT) and requires zygotic transcription. Cao et al . show that the F-box protein Bard is expressed in a narrow time window at the end of the MZT. Upon Bard expression, an SCF E3 ubiquitin ligase complex binds to Smaug, and Smaug is degraded. Loss of Bard results in failure to degrade Smaug, meaning Bard serves as a zygotic timer for Smaug clearance and an orderly MZT.